2011
DOI: 10.1111/j.1439-0310.2011.01900.x
|View full text |Cite
|
Sign up to set email alerts
|

Do Nest Light Conditions Affect Rejection of Parasitic Eggs? A Test of the Light Environment Hypothesis

Abstract: Discrimination of foreign eggs is one of the most studied aspects of host defences against avian brood parasites. Although many factors affecting host egg‐recognition processes have already been evaluated, only a few attempts have been made to test the importance of light conditions in microhabitats of host nests. Here, we examined whether the objectively measured nest light environment affects great reed warbler (Acrocephalus arundinaceus) responses towards real common cuckoo (Cuculus canorus) eggs. More spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 53 publications
(100 reference statements)
1
29
0
Order By: Relevance
“…An interesting and important question is whether cuckoos really profit from the host selection in our study area. Our recent study revealed that the great reed warblers recognize parasitic eggs based on the chromatic contrast, but only in well illuminated nests [60]. However, the chromatic contrast alone (calculated for UVS type of cones) did not differ between rejecters (n ¼ 16) and acceptors (n ¼ 23; Wilcoxon test, W ¼ 217, p ¼ 0.36, data from 2009 and 2010).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…An interesting and important question is whether cuckoos really profit from the host selection in our study area. Our recent study revealed that the great reed warblers recognize parasitic eggs based on the chromatic contrast, but only in well illuminated nests [60]. However, the chromatic contrast alone (calculated for UVS type of cones) did not differ between rejecters (n ¼ 16) and acceptors (n ¼ 23; Wilcoxon test, W ¼ 217, p ¼ 0.36, data from 2009 and 2010).…”
Section: Discussionmentioning
confidence: 88%
“…Therefore, egg discrimination under such light conditions may favour chromatic rather than achromatic visual signals [33,39]. Indeed, some studies confirmed that egg-rejection behaviour in bright light conditions depends primarily on chromatic rather than on achromatic contrast [23,24,60]. Such host behaviour may create a selection pressure on the cuckoo, which can gain an advantage if it chooses the correct host clutches on the basis of the chromatic signal.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence suggests that there is selective pressure for brood parasites to evolve dark, cryptic eggs among Australasian cuckoo-host systems, making egg detection by hosts or, rather, by competing parasites difficult because the eggs blend in with the nest background (Langmore et al, 2005(Langmore et al, , 2009Gloag et al, 2014). While similar arguments have also been made for other host-parasite systems (Mason and Rothstein, 1987;Honza et al, 2011Honza et al, , 2014, experimental tests of whether eggnest contrast affects parasitic egg discrimination in the context of both natural and experimental egg color variation are lacking.…”
Section: Introductionmentioning
confidence: 93%
“…In this model, we set the relative cone densities (UVS: 1, SWS: 1.78, MWS: 2.21, LWS: 1.96) based on cone density data measured by Hart et al (2000). Ambient light level irradiance data of a generic 'open-cup' nesting species were extracted from Avilés et al (2008) and were kindly provided by Igic et al (2012), as ambient light levels can affect both the risk of parasitism and parasitic egg detection (Langmore et al, 2005;Muñoz et al, 2007;Avilés, 2008;Honza et al, 2011). Achromatic contrasts were calculated by summing MWS and LWS cone spectra Vorobyev, 2005, 2008;Gomez, 2006), as their combined sensitivities are thought to be comparable to those of the noncolor-sensitive rod and double cone (Osorio et al, 1999) photoreceptors across avian taxa (Hart et al, 1998(Hart et al, , 2000Igic et al, 2009).…”
Section: Spectral Measurements and Visual Modelingmentioning
confidence: 99%
“…b The relationship between egg-nest contrast, plotted as the mean JNDs between unmanipulated host nest lining However, egg rejection behaviours of hosts are also influenced by the physical and biotic properties of the nest environment. Some of these factors include the intensity (Langmore et al 2005 ) and composition (Honza et al 2011 ) of the light illuminating the nest (Honza et al 2014 ), the number and colour of the other eggs in the nest (Lang et al 2014 ;Moskát et al 2014a ;Yang et al 2014 ), variation in the arrangement of the whole clutch (Polaciková et al 2013 ; but see Hanley et al 2015 ), and the prior presence of parasitic eggs in the clutch (Hauber et al 2006 ;Moskát and Hauber 2007 ;Moskát et al 2014b ). Similarly, important factors include the date of clutch initiation by the host (de Mársico et al 2013 ), and the presence of brood parasitic adults near the nest or in the breeding habitat (Davies and Brooke 1988 ;Mosknes and Røskaft 1989;Bártolet al 2002 ).…”
Section: Figmentioning
confidence: 99%